Antibiotic Stewardship and Its Impact on Antibiotic Use at The Child Health Directorate of A Teaching Hospital In Ghana (AFRICAN JOURNAL OF APPLIED RESEARCH, 2022)
Purpose: The study was intended to ascertain the existence of an antibiotic stewardship programme at the Child Health Directorate of Komfo Anokye Teaching Hospital (KATH) and assess the knowledge of health professionals about the importance of the antimicrobial stewardship programme.  Again, it sort to assess the experience of participants with pharmacotherapy of infections and patient outcomes with generic and innovative brands of antibiotics. The third was to assess reporting on adverse reactions and storage conditions of the antibiotics.Design/Methodology/ Approach: This was a cross-sectional study involving health professionals who participated in the provision of infectious disease management services. Findings:  Eighty-eight (88) professionals were involved in the study, comprising nurses (n=51), medical doctors (n=21), pharmacists (n=8), biomedical scientists (n=5) and public health officers (n=3). No antibiotic stewardship programme existed. However, there was a protocol for antibiotic use that was not strictly adhered to. About 60 % of the participants had knowledge of the antibiotic stewardship programme and affirmed its importance. The majority (75 %, n=66) reported treatment failure with generic brands of antibiotics compared to innovator brands. Thirty-four percent of the participants (n=30) reported adverse drug reactions (ADRs) on antibiotic therapy to superiors instead of filling out ADR forms.  Antibiotics were kept in inpatient bedside cabinets with no thermometers to monitor the storage temperature conditions.Research Limitations: The study was done in one Directorate in the hospital and thus cannot be generalized to reflect the situation in all teaching hospitals in Ghana.Practical implication: The evidence obtained highlighted the need for pragmatic antimicrobial stewardship (AMS) at the directorate to help optimize the management of childhood infections and minimize the emergence and spread of antibiotic resistance.Originality/Value. This was an original project designed to generate evidence to inform interventions to promote the responsible use of antimicrobials in children.